Delayed replantation after prolonged dry storage - Anita Rao; Apoorva Kommula; Muralidhar Tummala (Wolters Kluwer Medknow Publications, 2014)
Management of tooth avulsion in the permanent dentition often presents a challenge. Definitive treatment planning and consultation with specialists is seldom possible at the time of emergency treatment. Replantation of the avulsed tooth can restore esthetic appearance and occlusal function shortly after the injury. This article describes the management of a patient with an avulsed maxillary permanent incisor that had been air-dried for about 40 h. The replanted incisor retained its esthetic appearance and functionality 1 year after replantation, yet the long-term prognosis is not good because of progressive replacement root resorption.